A qualitative evaluation of an ethnic mental health and living skills support program. Issue 2 (2nd April 2016) - Eftimovska-Tashkovska, Julijana; Mullan, Judy; Vella, Shae-Leigh; Pitts, Leissa; Petkovski, Anica; Pai, Nagesh B.
ABSTRACT: Individuals with mental illness from culturally and linguistically diverse (CALD) backgrounds have poorer health outcomes than their non-CALD peers. Support groups have been found to be an effective component of the treatment for both affective and psychotic disorders. The aim of this study is to investigate participants' perceptions of a Macedonian Mental Health and Living Skills Program, a support group program for Macedonian individuals with a serious mental illness. Two focus groups were conducted with 22 CALD participants, with 11 participants in each group. The discussion centered on their perceptions and experiences of the group. The results indicated the following key themes that emerged from the focus group data: improved social opportunities; a sense of comfort and belonging; improved mood; increased motivation; better access to health information; and reductions in hospital admissions. In summary, the CALD participants perceived the support program to be highly beneficial and advantageous to their health and wellbeing.